1979
DOI: 10.1111/j.1471-0528.1979.tb10592.x
|View full text |Cite
|
Sign up to set email alerts
|

Computer Analysis of Fetal Heart Rate Variation During Normal Pregnancy

Abstract: Ninety-seven one-hour recordings of the abdominal fetal electrocardiogram (ECG) were made from 59 normal patients between 21 and 41 weeks of gestation. The heart intervals, measured between successive R-waves, were analysed by computer. The signal-to-noise ratio of the fetal ECG limited the precision of the interval measurements to approximately one millisecond. The characteristics of the baseline heart rate changed significantly as gestation advanced, the mean R-R interval, the standard deviation of the inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
24
0

Year Published

1980
1980
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(29 citation statements)
references
References 19 publications
5
24
0
Order By: Relevance
“…We have recently reported similar results in a case of gestational hypertension (SCHIERMEIER et al, 2005). The dependency of FHRV on gestational age, confirmed in this work, has been previously documented (WHEELER et al, 1979;VAN LEEUWEN et al, 1999;WAKAI, 2004). Beyond this, our results demonstrate that, in the assessment of FHRV, it is essential to take the heart rate, i.e.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…We have recently reported similar results in a case of gestational hypertension (SCHIERMEIER et al, 2005). The dependency of FHRV on gestational age, confirmed in this work, has been previously documented (WHEELER et al, 1979;VAN LEEUWEN et al, 1999;WAKAI, 2004). Beyond this, our results demonstrate that, in the assessment of FHRV, it is essential to take the heart rate, i.e.…”
Section: Discussionsupporting
confidence: 71%
“…One of these factors could be fetal activity which is known to influence FHRV from the 28th week of gestation onwards (PILLAI and JAMES, 1990). This corresponds roughly to the increasing spread of the HRV measures after the 30th week of gestation that we and others have observed (WHEELER et al, 1979;VAN LEEUWEN et al, 1999;WAKAI, 2004).…”
mentioning
confidence: 51%
See 1 more Smart Citation
“…It is known from previous studies that the heart rate of the human fetus decreases from month to month with the advancement of pregnancy (Wheeler et al, 1979;van Leeuwen et al, 1999). Nagel et al (2010Nagel et al ( , 2011 have found that the same occurs in the equine fetus, with an increase of HRV during gestation.…”
mentioning
confidence: 93%
“…In humans, the variability of fetal heart rate increases markedly in the third trimester of pregnancy. This can probably be attributed to the maturation of the vegetative nervous system which influences cardiac function (Wheeler et al, 1979;van Leeuwen et al, 1999).…”
mentioning
confidence: 99%